Cross-linking of a biopolymer-peptide co-assembling system - Inostroza-Brito,KE; Collin,EC; Majkowska,A; Elsharkawy,S; Rice,A; Hernandez,AEDR; Xiao,X; Rodriguez-Cabello,J; Mata,A (Acta Biomaterialia, 2017)
The ability to guide molecular self-assembly at the nanoscale into complex macroscopic structures could enable the development of functional synthetic materials that exhibit properties of natural tissues such as hierarchy, adaptability, and self-healing. However, the stability and structural integrity of these kinds of materials remains a challenge for many practical applications. We have recently developed a dynamic biopolymer-peptide co-assembly system with the capacity to grow and undergo morphogenesis into complex shapes. Here we explored the potential of different synthetic (succinimidyl carboxymethyl ester, poly (ethylene glycol) ether tetrasuccinimidyl glutarate and glutaraldehyde) and natural (genipin) cross-linking agents to stabilize membranes made from these biopolymer-peptide co-assemblies. We investigated the cross-linking efficiency, resistance to enzymatic degradation, and mechanical properties of the different cross-linked membranes. We also compared their biocompatibility by assessing the metabolic activity and morphology of adipose-derived stem cells (ADSC) cultured on the different membranes. While all cross-linkers successfully stabilized the system under physiological conditions, membranes cross-linked with genipin exhibited better resistance in physiological environments, improved stability under enzymatic degradation, and a higher degree of in vitro cytocompatibility compared to the other cross-linking agents. The results demonstrated that genipin is an attractive candidate to provide functional structural stability to complex self-assembling structures for potential tissue engineering or in vitro model applications.